2017
DOI: 10.1002/cpp.2129
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the acceptability of a positive psychology intervention versus a cognitive behavioural therapy for clinical depression

Abstract: There is growing evidence on the efficacy of positive psychology interventions (PPI) to treat clinical disorders. However, very few studies have addressed their acceptability. The present study aimed to analyse 2 key components of acceptability (i.e., client satisfaction and adherence to treatment) of a new PPI programme, the Integrative Positive Psychological Intervention for Depression (IPPI-D), in comparison to a standard cognitive behavioural therapy (CBT) programme in the treatment of clinical depression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 74 publications
(123 reference statements)
2
34
0
Order By: Relevance
“…In this analysis, baseline (0 months) and post-treatment (3 months) scores on the BDI-II were used. On average, participants were severely depressed (CBT: M = 37.42, SD = 10.68; IPPI-D: M = 34.66, SD = 10.13) and presented high comorbidity (Lopez-Gomez et al, 2017). Treatment condition was a binary variable and referred to either CBT or IPPI-D. Hypothesized predictors were measured at baseline and are displayed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this analysis, baseline (0 months) and post-treatment (3 months) scores on the BDI-II were used. On average, participants were severely depressed (CBT: M = 37.42, SD = 10.68; IPPI-D: M = 34.66, SD = 10.13) and presented high comorbidity (Lopez-Gomez et al, 2017). Treatment condition was a binary variable and referred to either CBT or IPPI-D. Hypothesized predictors were measured at baseline and are displayed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, the treatment selection method developed by DeRubeis et al (2014) was applied as a post-hoc analysis of data from a recently published trial comparing the efficacy of a CBT group intervention and a positive psychology group intervention (IPPI-D) for clinical depression Lopez-Gomez et al, 2017;Vazquez et al, 2018). Results showed that both intervention programs were statistically and clinically effective as well as highly acceptable for clinically depressed participants, with no significant differences either in the main (i.e., severity of depressive symptoms and clinical diagnosis) or secondary (e.g., emotional functioning, well-being) outcomes.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies, most of them investigating online programs, suggest that PPIs can lead to an increase in well‐being, a reduction in symptoms of depression as well as anxiety, and an increase in subjective health (Antoine, Dauvier, Andreotti, & Congard, ; Bolier, Haverman, Kramer et al, ; Görges, Oehler, Hirschhausen, von, Hegerl, & Rummel‐Kluge, ; Seligman, Rashid, & Parks, ; Seligman, Steen, Park, & Peterson, ; Shapira & Mongrain, ; Wellenzohn, Proyer, & Ruch, ; see Bolier & Abello, ; Mitchell, Vella‐Brodrick, & Klein, for reviews) . Recent studies comparing PPI and CBT group therapies suggest that PPIs are as effective as CBT interventions in treating severe clinical depression, while leading to even greater satisfaction scores among patients (Chaves, Lopez‐Gomez, Hervas, & Vazquez, ; Lopez‐Gomez, Chaves, Hervas, & Vazquez, ). However, results were not consistent across studies as others did not observe an improvement concerning symptoms of depression (Abbott, Klein, Hamilton, & Rosenthal, ; Gander, Proyer, Ruch, & Wyss, ; Mitchell, Stanimirovic, Klein, & Vella‐Brodrick, ; Mongrain & Anselmo‐Matthews, ; Sin, Della Porta, & Lyubomirsky, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, researchers also do not fully use behavioral psychology, but are also supported by cognitive behavioral therapy (CBT). Through this CBT, a person can get therapy, treatment, and handling a problem positively in the hope that it can produce positive things as well [12]; [11]; [3].…”
Section: Introductionmentioning
confidence: 99%